Synthesis and structure elucidation of some novel thiophene and benzothiophene derivatives as cytotoxic agents - Mohareb Rafat M.; Abdallah Amira E. M.; Helal Maher H. E.; Shaloof Somiya M. H. (Acta Pharmaceutica)
Attempting to produce cyclized systems with potential anti-proliferative activity, a series of novel thiophene and benzothiophene derivatives were designed and synthesized. The reactivity of the latter derivatives towards different chemical reagents was studied. Twenty-one compounds were synthesized and evaluated as anti-cancer agents. The results showed that ethyl 5-amino-3-(4-chlorostyryl)-4-cyanothiophene-2-carboxylate (5b), ethyl 5-amino-4-((4-methoxyphenyl)carbonyl)-3-methylhiophene-2-carboxylate (8c) and 5-3-(ethoxy-3-oxopropanamido)-3-methyl-4-(phenylcarbamoyl)thiophene-2-carboxylate (9) were the most active compounds towards three tumor cell lines – MCF-7 (breast adenocarcinoma), NCI-H460 (non-small cell lung cancer) and SF-268 (CNS cancer) and a normal fibro-blast human cell line (WI-38) compared to the anti-proliferative effects of the reference control doxorubicin.